REVIEWING BEST SELLER BILINGUAL ENGLISH INDONESIAN SHORT STORIES BASED ON SHORT-STORY PHILOSOPHY - Helmanto, Fachri; Hidayat, Arif (Universitas Gunadarma, 2023)
Most people relate storytelling into an activity with some improvisation to make vivid ideas, emotion and beliefs through story. Storytelling needs a story consisting of theme, characters and plot. Reviewing the philosophy of short-story, it consists single character, single event and single emotion or series of emotion. this study is intended to investigate whether or not the short story in Indonesian is following the short-story philosophy. This study is using content analysis of 15 bilingual English Indonesian best seller short stories. The data are analyzed by applying the philosophy of short story. The data findings are validate using investigator triangulation. The result of this study reveals that best seller of short stories only 6 of 15 books which follow the short story philosophy. It is suggested the rest books should be elaborate more to novel. For further research, as technology rapidly developed and the story has to give more emotion to readers. The storytellers or researcher is recommended to develop story scaping as a new structure of short story.